Enchondroma Protuberans of Ulnar Bone: A Case Report and Review of Literature - Afshin Mohammadi; Abbas Hedayati Asl; Mohammad Ghasemi-Rad; Farahnaz Noroozinia (Case Reports in Radiology)
Introduction. Enchondroma protuberans is an extremely rare benign cartilaginous bone tumor. We report the first case report of enchondroma protuberans in the forearm. Presentation of Case. We report a case of enchondroma protuberans originating in the left ulnar bone of a young woman. A 20-year-old female referred to our hospital complaining of progressive sustained left forearm pain with a radiation to fourth and fifth finger. Conventional radiography revealed a well-defined eccentric osteolytic lesion in the distal diaphysis of ulna with expansion of overlying cortex (without calcification). Magnetic resonance imaging showed a well-defined ovoid intramedullary lesion, which was exophytically protruding from medial surface of left ulnar bone. Histopathology confirmed the diagnosis. Discussion. Enchondroma protuberans typically present as a well-defined intramedullary osteolytic lesion that may be accompanied by a fine matricidal calcification. The connection between the intramedullary portion and the exophytic protrusion can be seen well by magnetic resonance imaging. Conclusion. Enchondroma protuberans should be considered in the differential diagnosis of osteochondroma, enchondroma, and periosteal chondroid tumors.